The Juridical Criminal Construction of Corruption Extortion in Taxation Sector Related to State Financial Losses - Perdana, Lilik; Wahyuningsih, Sri Endah (Universitas Islam Sultan Agung, 2021)
The purpose of this article is to analyze the juridical construction of the criminal act of extortion corruption in the taxation sector. The method used is normative juridical, both in the narrow sense and in the broad sense. While the analysis orientation is in the form of a conceptual approach (Concept Approach) and a statutory approach (Statue Approach). The results of the research obtained are the primary indictment model, Article 12 letter e of the Anti-Corruption Law in conjunction with Article 55 paragraph (1) of the 1st Criminal Code. Subsidiary, Article 23 of the Anti-Corruption Law in conjunction with Article 421 in conjunction with Article 55 paragraph (1) of the 1st Criminal Code as a fulfillment of its legality principle. Meanwhile, the principle of culpability is in the form of the defendant's intentional coercion of the taxpayer through his role as a person to participate in committing a crime (medepleger).